PENDAMPINGAN MANAJEMEN RITEL MODERN BAGI KOMUNITAS PEDAGANG RITEL TRADISIONAL PASAR DINOYO KOTA MALANG - Wahyuni, Nanik; O, Ulfi Kartika; Rahayu, Yayuk Sri (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2020)
The purpose of this service is to provide assistance related to retail management for traditional traders in Malang Dinoyo Market in order to be able to compete with modern traders. The strategy undertaken is through the stages of customer identification and Dinoyo Market traders, observation and conducting Forum Group Discussions (FGD) with assistance in the form of management of spatial and merchandise management, assistance in preparing simple financial statements and management of merchandise inventory. The result of this dedication is the increasing knowledge of Dinoyo Market traders in selling their merchandise so that the bias can still exist in modern times like today.